Combined weak-current discharge in a copper-vapor laser; Technical Physics; Vol. 61, iss. 9 - Fedorov V. F. Valery Fedorovich; Shiyanov D. V. Dmitry Valeryevich; Fedorov K. V. Kirill Valerjevich; Evtushenko G. S. Gennady Sergeevich; Torgaev S. N. Stanislav Nikolaevich; Kulagin A. E. Anton Evgenievich (2016, 2016)
Title screen